The Ischial Spine in Developmental Hip Dysplasia: Unraveling the Role of Acetabular Retroversion in Periacetabular Osteotomy - Gerard El-Hajj; Hicham Abdel-Nour; Rami Ayoubi; Joseph Maalouly; Fouad Jabbour; Raja Ashou; Alexandre Nehme (Advances in Orthopedics)
Purpose. Radiological diagnosis of acetabular retroversion (AR) is based on the presence of the crossover sign (COS), the posterior wall sign (PWS), and the prominence of the ischial spine sign (PRISS). The primary purpose of the study is to analyze the clinical significance of the PRISS in a sample of dysplastic hips requiring periacetabular osteotomy (PAO) and evaluate retroversion in symptomatic hip dysplasia. Methods. In a previous paper, we reported the classic coxometric measurements of 178 patients with symptomatic hip dysplasia undergoing PAO where retroversion was noted in 42% of the cases and was not found to be a major factor in the appearance of symptoms. In the current study, we have added the retroversion signs PRISS and PWS to our analysis. Among the retroverted dysplastic hips, we studied the association of the PRISS with the hips requiring PAO. We also defined the ischial spine index (ISI) and studied its relationship to the coxometric measurements and AR. Results. In hips with AR, the operated hips were significantly associated with the PRISS compared to the nonoperated ones (χ2 = 4.847). Additionally, the ISI was able to classify acetabular version (anteverted, neutral, and retroverted acetabula). A direct correlation between the ISI and the retroversion index (RI) was found, and the highest degree of retroversion was found when the 3 signs of acetabular retroversion were concomitantly present (RI = 33.6%). Conclusion. The PRISS, a radiographic sign reflecting AR, was found to be significantly associated with dysplastic hips requiring PAO where AR was previously not considered a factor in the manifestation of symptoms and subsequent requirement for surgery. Moreover, the PRISS can also serve as an adequate radiographic sign for estimating acetabular version on pelvic radiographs.